Performance Analysis of All-optical Logic Gates Based on Cross-phase Modulation in an Asymmetric Coupler - Aggarwal, Abha (My University, 2015)
The importance of fiber optic communication is increasing at very fast pace in today’s world. The demand for transmission in broadband internet services for data transmission like real time video conferencing and in telecommunication network over the globe is growing at an exponential rate and only fiber optics communication networks are able to meet this challenge. Optical fiber communication systems are being extensively used all over the world for telecommunication, video and data transmission purposes. This is because of the huge capacity of optical fiber. It can provide data rates in Tbps over optical fiber by wavelength division multiplexing techniques. Switching function is very important in information processing in optical networks. The recent trend is to design All optical network elements in optical signal processing which eliminate use of costly high speed electronics because they don’t need optical toelectronic- to-optical' conversion. In our thesis work, we investigated Nonlinear Fiber Directional Coupler which has technological applications in power splitting, wavelength division multiplexing, demultiplexing, polarization splitting and fiber optic sensing. We analyzed the switching characteristics of nonlinear directional fiber coupler in presence of Kerr nonlinearity. We introduce a pulse into the nonlinear directional coupler, and add a pump light by wavelength division multiplexing which is to use Kerr effect as an advantage and produce the cross-phase modulation. We then analytically solve the coupled nonlinear Schrodinger equations for the input power and plot transmission coefficient with respect to normalized input power for varying values of coupling coefficient. After that, we analyse the effect of coupling coefficient on the switching characteristics i.e. transmission coefficient with respect to normalized input power with input signal in one port and input signal in both the ports respectively. We analyse that by increasing the value of coupling coefficient K, the maximum value of transmission coefficient for core 1 decreases and the minimum value of transmission coefficient for core 2 increases and by increasing the value of K, the input power for peak value of transmission coefficient also increases. We also observe that by increasing the value of coupling coefficient from 0.05 to 0.1 the graph for pump power are reversed. We study the effect of different values of gain of core 1 and core 2 on the extinction ratio. It can be seen that OR gate. a XOR gate and a new logic expression has been realized.
M.E. (ECED)
Keywords: All optical logic gates; cross phase modulation; ECED